2006
DOI: 10.1017/s1368980006009803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a brief pilot nutrition and exercise intervention for the prevention of weight gain in general practice patients

Abstract: Objective: To pilot-test a brief written prescription recommending lifestyle changes delivered by general practitioners (GPs) to their patients. Design: The Active Nutrition Script (ANS) included five nutrition messages and personalised exercise advice for a healthy lifestyle and/or the prevention of weight gain. GPs were asked to administer 10 scripts over 4 weeks to 10 adult patients with a body mass index (BMI) of between 23 and 30 kg m 22 . Information recorded on the script consisted of patients' weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A mentioned study in Australia, also, showed that obese patients suffering from high blood pressure were more often provided with nutritional advice by their GP, as opposed to obese patients who did not suffer from high blood pressure. A study among Australian doctors, as well as other studies, stressed that some GPs are more likely to provide nutrition counselling to individuals with specific health risks, especially if they suffer from more than one risk [ 13 , 14 ]. This study shows a greater ratio of Croatia’s GPs provide nutritional advice to patients with some risks, as opposed to the ratio of those who provide nutrition counselling for all patients, regardless of their individual risks.…”
Section: Discussionmentioning
confidence: 99%
“…A mentioned study in Australia, also, showed that obese patients suffering from high blood pressure were more often provided with nutritional advice by their GP, as opposed to obese patients who did not suffer from high blood pressure. A study among Australian doctors, as well as other studies, stressed that some GPs are more likely to provide nutrition counselling to individuals with specific health risks, especially if they suffer from more than one risk [ 13 , 14 ]. This study shows a greater ratio of Croatia’s GPs provide nutritional advice to patients with some risks, as opposed to the ratio of those who provide nutrition counselling for all patients, regardless of their individual risks.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis, however, needs further investigation. Another implication of these results is that the sedentary state, at least in rodents, should not be considered as the proper control condition because physical activity and health are inevitably linked (Booth et al, 2006). This point is illustrated by the healthy insulin profiles in the voluntary running passively coping RLA rats.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents' level of confidence to provide nutrition care to overweight adults is of concern given the current emphasis by public health agencies to address Australia's high rates of overweight and obesity 23 and acknowledgement that GPs require appropriate nutrition knowledge to prevent and manage chronic diseases. 24 Evidence exists that GPs target obese patients for weight loss ahead of overweight patients suggesting the use of weight loss as an intervention rather than as a preventive health care strategy. 25 It is of concern that GPs do not feel confident to provide nutrition care to all groups of patients and for the range of nutritional recommendations to reduce cardiovascular risk.…”
Section: Insert Table Two About Herementioning
confidence: 99%